2022
DOI: 10.1108/tpm-07-2021-0049
|View full text |Cite
|
Sign up to set email alerts
|

The effects of working agile on team performance and engagement

Abstract: Purpose This study aims to examine the relationship between the agile way of working and team performance and engagement. Furthermore, psychological safety climate was investigated as a mediator of this relationship. As organizations are increasingly adopting the agile way of working method beyond the information technology (IT) setting, the authors researched its effects in teams across a variety of functional domains. Design/methodology/approach Survey data was collected from 97 agile teams working in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 48 publications
(103 reference statements)
7
38
0
Order By: Relevance
“…In addition, individuals in agile teams report high levels of psychological empowerment resulting from both regular team interaction and support, and greater team responsibility [32]. In agile teams, structures with fewer hierarchies, higher levels of autonomy, and increased team motivation are created, which in turn can lead to a higher level of job satisfaction [12,40,41], affective organizational commitment [9], and work engagement [42,43]. Furthermore, by promoting agile work practices within the organization, attractive and people-oriented values such as respect, courage, and commitment come into sharper focus and change the way team members feel [23].…”
Section: Total Effects Of Agile Work Practices On Occupational Well-b...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, individuals in agile teams report high levels of psychological empowerment resulting from both regular team interaction and support, and greater team responsibility [32]. In agile teams, structures with fewer hierarchies, higher levels of autonomy, and increased team motivation are created, which in turn can lead to a higher level of job satisfaction [12,40,41], affective organizational commitment [9], and work engagement [42,43]. Furthermore, by promoting agile work practices within the organization, attractive and people-oriented values such as respect, courage, and commitment come into sharper focus and change the way team members feel [23].…”
Section: Total Effects Of Agile Work Practices On Occupational Well-b...mentioning
confidence: 99%
“…Following the suggestion of Junker et al [5], it would be interesting to see in which contexts agile work practices have positive outcomes for individual well-being and in which contexts they might not. Study results have already shown that the agile way of working can be beneficial for teams beyond IT by being positively associated with the psychological safety climate, engagement, and performance of various functional areas of a bank [43]. However, it also has been discussed that agile teamwork does not necessarily unfold the benefits in every context [89].…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Laanti (2013) found that 64% of teams that were adapting to the agile methodologies scrum or Kanban felt that their performance did increase after taking the methodologies into use. Peeters et al (2022) studied 97 agile teams and found that the agile way of working positively relates to team performance and engagement. Similarly, a case study by Mann and Maurer (2005) observed a higher subjective work quality as well as an increased customer satisfaction for teams working with the agile methodology scrum, over the course of 2 years.…”
Section: Learningmentioning
confidence: 99%
“…Further investigation from Peeters et al (2022) was carried out using data from a financial sector multinational firm renowned for agile working. A questionnaire was completed by 97 teams operating in ten different countries.…”
Section: Evidence From a Multinational Organizationmentioning
confidence: 99%